EFEKTIVITAS PROGRAM "AL-KAHFI TIME" DALAM MENINGKATKAN PEMBIASAAN MEMBACA SURAT AL-KAHFI DI KALANGAN MAHASISWA - Hanif Pratista Anggara; Hayumuti Hayumuti; Mukhammad Bakhruddin (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to analyze the effectiveness of the Al-Kahfi Time program in forming the habit of reading Surah Al-Kahfi every Friday among students of the Faculty of Islamic Religion, Universitas Muhammadiyah Surabaya (UMSurabaya). This research approach uses a qualitative method with a case study design. Data were obtained through in-depth interviews with Jam'iyyatul Qurra' Wal Huffadz administrators, direct observation of activities, and document analysis related to program implementation at the UMSurabaya Mosque. The results showed that the Al-Kahfi Time program contributed positively to increasing students' spiritual awareness and habituation to reading Surah Al-Kahf consistently. Increased understanding of the importance of the Prophet's sunnah can be seen from the consistency of program participants, which is supported by a conducive community environment and technology-based reminders. However, challenges such as academic schedule conflicts, lack of student participation from the Muhammadiyah Student Association, and limited variety of implementation strategies remain. The program has only been running for one year so further development is needed. The researcher concludes that these results demonstrate the effectiveness of the program in shaping students' positive habits, with recommendations to expand participation and make optimal use of digital technology. This research contributes to the development of a community-based program that integrates spiritual values in life.